Analisis motivasi belajar siswa dalam menemukan gagasan pokok pada paragraf teks bacaan kelas IV D di sekolah dasar - EvritaNurdiana AnggitaSari; Rukayah Rukayah; Siti Kamsiyati (Didaktika Dwija Indria, 2021)
The goal of this research were 1) to describe the implementation of Indonesian language learning, and 2) to describe students' learning motivation in finding the main idea of paragraphs in grade IV SD Djama’atul Ichwan Surakarta. The method applied in this research is descriptive analysis. Data collection techniques in this study were interviews, observation, and documentation study.. This study used a validity test technique in the form of triangulation of data and sources. The data were then analyzed using interactive data analysis techniques by Miles and Huberman, namely data reduction, data presentation, and conclusion drawing/ verification. The result is there are 3 students who have high motivation and 3 students who have low motivation. The indicator that has not been fulfilled by most subjects is the good use of time, while the indicator that is fulfilled by all subjects is being able to work independently .The category of learning motivation that is owned by most of the fourth grade students is external motivation. The  research implication can add references and insights for further research and be used as a reference for teachers and students related to learning motivation in finding the main ideas in paragraphs.